2020
DOI: 10.1039/c9sc03653a
|View full text |Cite
|
Sign up to set email alerts
|

The electron as a probe to measure the thickness distributions of electroactive films

Abstract: A theoretical model combined to an experimental study shows that the morphology of electron conducting films can be quantified directly from the analysis of cyclic voltammetry data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(59 reference statements)
0
9
0
2
Order By: Relevance
“…The electroactive thickness distributions of the films were subsequently investigated through cyclic voltammetry. 32 The main benefit of using an electroanalytical method in comparison to AFM is that it probes the portion of the film that is accessible to electrons and therefore, the portion of the film matrix that is break-free and able to contribute to electrochemical processes. Additionally, the whole surface of the electrode is probed instead of a selected area.…”
Section: Resultsmentioning
confidence: 99%
“…The electroactive thickness distributions of the films were subsequently investigated through cyclic voltammetry. 32 The main benefit of using an electroanalytical method in comparison to AFM is that it probes the portion of the film that is accessible to electrons and therefore, the portion of the film matrix that is break-free and able to contribute to electrochemical processes. Additionally, the whole surface of the electrode is probed instead of a selected area.…”
Section: Resultsmentioning
confidence: 99%
“… 60 The authors demonstrated that deviations from the ideal behavior described above could be used to estimate film roughness, quantified as an ensemble thickness distribution. 59 These are important parameters to measure and optimize (surface roughness, film thickness, and charge transport diffusion coefficients), since they are tied to the reaction-diffusion behavior of the system, as demonstrated by the Thiele modulus, and inevitably control catalytic performance, which we will see in the following sections.…”
Section: Charge Transport Dynamicsmentioning
confidence: 99%
“…[17] Thee lectroactive film thickness distribution was quantified using an electroanalytical method based on linear sweep voltammetry. [18] Ther elative standard deviation in thickness of at hin film of V 2+ -PVA/FNR (8/1.1 mgcm À2 )w as 80 %( Figure S6) which reflects asignificantly higher degree of homogeneity in comparison to previously reported viologen modified polymer films. [17] In the presence of NADP + ,t he electrodes modified with V 2+ -PVA/FNR film generate cathodic catalytic current with ah alf-wave potential (À442 mV vs.S HE) near the formal redox potential of the viologen (Figure 1B).…”
Section: Angewandte Chemiementioning
confidence: 62%
“…The electrocatalytic properties of the modified electrodes are defined by the electroactive film thickness [16] and therefore a uniform film morphology is desired [17] . The electroactive film thickness distribution was quantified using an electroanalytical method based on linear sweep voltammetry [18] . The relative standard deviation in thickness of a thin film of V 2+ ‐PVA/FNR (8/1.1 μg cm −2 ) was 80 % (Figure S6) which reflects a significantly higher degree of homogeneity in comparison to previously reported viologen modified polymer films [17] …”
Section: Resultsmentioning
confidence: 99%